Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Wisatawan Di Taman Alam Lumbini Berastagi - Yestiara Litna Boru Barus; Natalia E.T. Sihombing; Kepler Sinaga (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study aims to analyze the influence of service quality and facilities on tourist satisfaction at Lumbini Berastagi Nature Park, both partially and simultaneously. Lumbini Nature Park is a leading natural and religious tourism destination in Karo Regency that offers the beauty of pagoda architecture and a spiritual atmosphere. Along with the increase in tourist visits to the Berastagi area, understanding the factors that drive visitor satisfaction is crucial for the sustainability of destination management. The research method used is a quantitative approach with a sample of 96 respondents determined using the Lemeshow formula. Data were collected through questionnaires and analyzed using multiple linear regression, classical assumption tests, and hypothesis tests (t-test and F-test) using SPSS 27 software. The results showed that service quality (X_1) has a positive and significant effect on tourist satisfaction (Y) with a t_{count} value of 2.992 > t_{table} 1.985. Likewise, the facility variable (X_2) has a positive and significant effect with a t_{count} value of 5.966 > t_{table} 1.985. Simultaneously, both variables have a significant effect with an F_{count} value of 21.466 > F_{table} 3.09 and a significance level of 0.000. The coefficient of determination (R^2) value of 30.1% indicates the contribution of the independent variables in explaining tourist satisfaction, while the rest is explained by other factors outside this study. This study recommends that managers prioritize facility maintenance as the most dominant factor in influencing visitor satisfaction.